Drought risk modelling for thermoelectric power plants siting using an excess over threshold approach. (1st January 2014) - Bekera, Behailu B.; Francis, Royce A.; Omitaomu, Olufemi A.
Water availability is among the most important elements of thermoelectric power plant site selection and evaluation criteria. With increased variability and changes in hydrologic statistical stationarity, one concern is the increased occurrence of extreme drought events that may be attributable to climatic changes. As hydrological systems are altered, operators of thermoelectric power plants need to ensure a reliable supply of water for cooling and generation requirements. The effects of climate change are expected to influence hydrological systems at multiple scales, possibly leading to reduced efficiency of thermoelectric power plants. In this paper, we model drought characteristics from a thermoelectric systems operational and regulation perspective. A systematic approach to characterise a stream environment in relation to extreme drought occurrence, duration and deficit-volume is proposed and demonstrated. This approach can potentially enhance early stage decisions in identifying candidate sites for a thermoelectric power plant application and allow investigation and assessment of varying degrees of drought risk during more advanced stages of the siting process.